A LITERARY REVIEW ON MENTORING IN THE EASTERN WORLD - Molligoda, S.P.; Sooriyaarachchi, B.S.M.M.; Palathiratne, S.M. (World Journal of Pharmaceutical Research, 2020)
Mentorship denotes a relationship in which a more experienced or more knowledgeable person helps to guide a less experienced or less knowledgeable person. Mentoring has become a worldwide talking issue in the present day scenario. For a particular individual, mentoring can be done in various ways and at diverse stages. This is widely used parlance in many fields and it has been penetrated in to wide spectrum of subject areas namely; higher education, management, administration, economics and others. Thus, it is not confined only to a particular domain and it is not possible to give a specific demarcation. This is not totally different from counseling, but it embraces multipronged nuance of meanings and in other ways goes beyond the apparent meaning too. Many Western philosophers hold dissecting and propagating views on mentoring, but on the other hand the mentorship was an integral part of the Eastern philosophy, since times immemorial. The main objective of this research paper is to probe and thoroughly investigate in-to various spheres of mentoring in the Eastern world. For the present review study; texts of Indian philosophy, main Samhita of Ayurveda, other available resources in various languages, published articles in peer reviewed journals, related material available online, dictionaries and encyclopedia were referred to compile, analyze and interpret data in a methodical and rational manner. Primary distinction observed between the philosophy of mentoring in the West and the East is that the, ancient people of the East consider the spiritual aspect of the mentor more than thoseof the West. In a nutshell, the bipod of mentorship can stand at success, only if both the mentor and mentee are enriched with the proper attributes and above all a will to dedicate for a common goal.
Keywords: Mentoring; Eastern; Philosophy; Samhita; Ayurveda